Guarantees of Interrogation the accused in Kuwaiti and comparative legislation: An analytical study - Alhajeri, Nayef Shafi Almudhafrah (Journal of Economic, Administrative and Legal Sciences, 2022)
The study aimed at identify the guarantees of interrogating the accused in Kuwaiti and comparative law, the study curriculum revolves around the legal approach, which presents the various legal and legislative frameworks, whether in the State of Kuwait or other countries, and related to the subject of our current study, which is the guarantees of questioning the accused in Kuwaiti and comparative law. Our current study will also use the comparative approach to identify the differences between Kuwaiti legislation and other legislation regarding the current study subject. Results shows that The right of defense is a basic pillar of the fairness of the criminal trial, and it occupies the top of its guarantees without dispute, and The constitutional legislator in Kuwait considered that individual rights and freedoms are the basis of all freedoms, and they may not be restricted or derogated from, and the state has a duty to protect these rights. And The Kuwaiti legislator has included the guarantee of the accused’s use of a lawyer with legal protection, and even arranged for violating this guarantee a strict penalty, which is the invalidity of the act and the procedure if it is done without enabling the lawyer to attend with the accused during the investigation stage. In light that We recommend the criminal procedural legislator in Kuwait to pay attention to the suspect’s right to the assistance of a lawyer, since the inference stage must take into account all the guarantees related to the rights of the defense. And We recommend the policemen in Kuwait to inform the suspect of the facts he is accused of committing, the evidence presented against him, in addition to the suspect’s knowledge of the type of investigation that is being conducted with him, and his decision to speak or remain silent. And We suggest to the Kuwait Bar Association to activate a committee of experienced lawyers to spread the legal culture in the community and introduce the right to defense in international constitutions and covenants, and introduce the professional rules that govern the relationship between the lawyer and the accused. Finally If the criminal procedural legislator in Kuwait has decided to guarantee the assistance of a lawyer for the accused in the investigation and trial stages, we recommend that this guarantee continue with the accused even during the execution of the sentence by including prison regulations against the prisoner with the assistance of a lawyer in disciplinary trials, as the imprisoned accused has the right to enjoy With the guarantees and rights granted to the ordinary person, and to the provisionally imprisoned.
Keywords: interrogation; The accused; Kuwaiti legislation; Comparative Legislation